Implementasi maqasid al-shari’ah sebagai solusi problematika sosial dan kemasyarakatan kontemporer - A . Bahruddin (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2017)
Islam as a legal system based on the Qur’an and sunnah ideally expected to be able to control the sociallife in society, by ensuring the implementation of their rights as individuals and society. Besides, as ameans of social control of the social changes that are happening in the life of society, as well as socialengineering tools in realizing the benefits in the world and the hereafter and maintain human dignity asa goal for the establishment of the law itself. Furthermore how is the ability of Islam in responding tothe growing demands of society in accordance with the times. So its ability to answer these challenges byproviding solutions to emerging social problems is a reality that is difficult to avoid, because peopleneed legal certainty as well as their rights both as individuals and communities need to get certainty as amanifestation of their rights in a fundamental way. Departing from these issues, the understanding ofIslamic law and the purpose of its implementation (Maqashid al-Shariah) becomes very important, itwill affect the success in the process of implementation of Islamic law both among Muslims and societyat large. So ideally Islamic law in reality in society is expected to provide legal protection for certain and asa tool of social control of social changes that occur in the life of society, and no less important is torealize the benefits and maintain human dignity as the purpose of the implementation of the law.